Education Conception between the National Curriculum and Modern Islamic Boarding Schools in Adjusting the 21st Century Development in SMA Al-Izzah Batu - Mochammad Soleman; Anoesyirwan Moeins; Iman Sofian Suriawinata (Indonesian Journal of Business, Accounting and Management (IJBAM), 2020)
The purpose of this study was to determine: (1) the socio-cultural situation in modern pesantren education. (2) the main substance of the content standard in the learning management instrument of modern Islamic boarding schools, and (3) the application of the standard concept of the education management process and its relation to the standard system of national education management and modern Islamic boarding schools at Al-Izzah Batu High School. This research method is qualitative with a case study approach. Primary data in the form of in-depth interviews with the head of the pesantren, the principal, the deputy for the curriculum, teaching staff, the head of the pesantren, students or santri Secondary data is in the form of observation and documentation study of all supporting documents related to the sub-focus, including institutional documents, which contain objectives, vision and mission, curriculum documents, and other relevant documents. Based on the results of data analysis, it can be concluded as follows: (1) culturally the existence of Al-Izzah High School can color the surrounding area by making Islamic areas by providing guidance to the community, (2) the curriculum is integrated into learning tools in the form of a syllabus and lesson plans, and (3) the National Curriculum and the Modern Islamic Boarding School Curriculum are applied in two ways, namely integrated in Teaching and Learning Activities and habituation activities by paying attention to school indicators and predetermined class indicators..